2019
DOI: 10.1073/pnas.1808016116
|View full text |Cite
|
Sign up to set email alerts
|

More than 18,000 effectors in the Legionella genus genome provide multiple, independent combinations for replication in human cells

Abstract: The genusLegionellacomprises 65 species, among whichLegionella pneumophilais a human pathogen causing severe pneumonia. To understand the evolution of an environmental to an accidental human pathogen, we have functionally analyzed 80Legionellagenomes spanning 58 species. Uniquely, an immense repository of 18,000 secreted proteins encoding 137 different eukaryotic-like domains and over 200 eukaryotic-like proteins is paired with a highly conserved type IV secretion system (T4SS). Specifically, we show that euka… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
274
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(292 citation statements)
references
References 47 publications
(51 reference statements)
2
274
0
1
Order By: Relevance
“…In addition, these regulatory systems have been shown to assemble into an interconnected regulatory network using accessory components, such as modulators (AckA-Pta and PTS Ntr [22,38]) and connectors (LetE and LerC [22,39,40]). All the direct regulators of EEGs described above (PmrA, CpxR, CsrA, Fis1, Fis3, and Fur) were found to be present in all the Legionella species examined (41,42), and they function as global regulators that regulate the expression of a large number of genes, including EEGs, scattered throughout the L. pneumophila genome (18)(19)(20)22). Besides global regulators, local regulators that regulate the expression of a small number of adjacent genes are also common in many bacterial systems (43,44), including pathogenesis-related genes in Vibrio cholerae and Salmonella enterica (45).…”
mentioning
confidence: 93%
“…In addition, these regulatory systems have been shown to assemble into an interconnected regulatory network using accessory components, such as modulators (AckA-Pta and PTS Ntr [22,38]) and connectors (LetE and LerC [22,39,40]). All the direct regulators of EEGs described above (PmrA, CpxR, CsrA, Fis1, Fis3, and Fur) were found to be present in all the Legionella species examined (41,42), and they function as global regulators that regulate the expression of a large number of genes, including EEGs, scattered throughout the L. pneumophila genome (18)(19)(20)22). Besides global regulators, local regulators that regulate the expression of a small number of adjacent genes are also common in many bacterial systems (43,44), including pathogenesis-related genes in Vibrio cholerae and Salmonella enterica (45).…”
mentioning
confidence: 93%
“…It is well established that Legionella effectors harbor domains typically found in eukaryotic proteins, such as ankyrin, F-box, and U-box domains and more (36,37,48,49). The analysis performed here indicates that the three novel PI3P-binding domains identified, even though not homologous to eukaryotic PI-binding domains, share the same amino acids critical for PI binding (22).…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies have shown that the Legionella genus contains thousands of effectors (35,36). These effectors are expected to function inside host cells during infection and to modulate host cell processes to the benefit of the bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is remarkable that some of them have evolved as mimics of eukaryotic nuclear proteins, either through sequence homologies (e.g., ANK, LRR, MYND, SET, F-box, U-box) or through true structural innovations (e.g., NEL domain). Interestingly, computational biology approaches suggest the presence of many uncharacterized proteins with potential nucleomodulin domains in the genomes of intracellular bacteria, such as Anaplasma [113], Legionella [114], and other species [115,116]. This opens up an important field of research into their functional roles.…”
Section: Resultsmentioning
confidence: 99%